Polyethyleneimine-Supported Triphenylphosphine and Its Use as a Highly Loaded Bifunctional Polymeric Reagent in Chromatography-Free One-Pot Wittig Reactions - Xia, Xuanshu; Toy, Patrick H. (Synlett, 2015)
A polyethyleneimine-supported triphenylphosphine reagent has been synthesized and used as a highly loaded bifunctional homogeneous reagent in a range of one-pot Wittig reactions that afforded high yields of the desired products after simple purification procedures. The approach also served efficiently in tandem reaction sequences involving a one-pot Wittig reaction followed by conjugate reduction of the newly formed alkene product in situ. In these transformations, the phosphine oxide groups generated in the Wittig reaction served as the catalyst for activating trichlorosilane in the subsequent reduction reaction.
Keywords: conjugate reduction; polyethyleneimine; polymer supported reagents; triphenylphosphine; Wittig reactions